Matrix operator models of waveguide bends - Petrusenko, I; Sanli, A (IEEE, 2004)
A novel rigorous solution of the problem of mode diffraction by the uniform bend of a guide is presented. The full-wave model is obtained via the matrix operator technique. This model has the form of Cayley's transformation between the sought-for reflection and the given accretive operator. Its correctness is proved analytically. The approach proposed can be efficiently applied to the analytic-numerical analysis of any abrupt waveguide junction.
10th International Conference on Mathematical Methods in Electromagnetic Theory -- SEP 14-17, 2004 -- Dnepropetrovsk, UKRAINE
Keywords: Section